2014
DOI: 10.3844/ajmsp.2014.37.40
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF ANTIMICROBIAL ACTIVITY IN OLIVE (<I>OLEA EUROPAEA</I>) LEAF EXTRACT

Abstract: In this study the antimicrobial activity of Olive Leaf Extracts (OLE) was screened against five grampositive and five gram-negative bacteria. The antimicrobial activity was evaluated using disc diffusion and microdilution methods. The diameters of inhibition zones of the olive leaf extract were observed 13.33±2.08 mm against S. typhimurium and 21.67±1.53 mm against B. cereus. There was a similarity between the inhibition zones of olive leaf extract and Gentamicin discs against S. typhimurium, P. vulgaris and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
2
17
0
2
Order By: Relevance
“…(2003) also reported that olive leaves have antimicrobial activity against E. coli, S. aureus, B. cereus and S. typhi . The results reported in the present study show similarity with previous ones (Markin et al., 2003; Pereira et al., 2007; Sudjana et al., 2009; Lee and Lee, 2010; Gökmen et al., 2014) about the antimicrobial activity of olive leaves extracts. According to Pereira et al.…”
Section: Resultssupporting
confidence: 92%
“…(2003) also reported that olive leaves have antimicrobial activity against E. coli, S. aureus, B. cereus and S. typhi . The results reported in the present study show similarity with previous ones (Markin et al., 2003; Pereira et al., 2007; Sudjana et al., 2009; Lee and Lee, 2010; Gökmen et al., 2014) about the antimicrobial activity of olive leaves extracts. According to Pereira et al.…”
Section: Resultssupporting
confidence: 92%
“…In a study by M. Gökmen et al (25) in 2015, the MIC value of olive leaves against Listeria monocytogenes, E. coli, and Pseudomonas aeruginosa was more than 32 mg/ml. This value was higher than 16 mg/ml for Bacillus cereus and S. aureus and Enterococcus faecalis and some other bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the OME was highly active (≥ 15 mm) against MRSA3, at all the extracts concentrations (1.875 -6.25 mg/well), and against all the test MRSA isolates at concentration 6.25 mg/well, while the extract (OME) was moderately active (ZDI: 12 -13 mm) against MRSA2 (at 1.875 -3.125 mg/well of OME) and against MRSA1 with 3.125 mg/well of OME; herein, the OSE had less to moderate activity against the MRSA isolates tested, based upon the previously mentioned criteria 11 . Gokmen et al 32 demonstrated the growth inhibition property of olive leaf extract against S. aureus having ZDI value of 19 mm.…”
Section: Resultsmentioning
confidence: 99%